Critical reflection: a student's perspective on a 'pedagogy of discomfort' and self-compassion to create more flexible selves. Issue 5 (3rd September 2021) - Robinson, Kristen
ABSTRACT: In this paper, I explore Fook's model of 'Critical Reflection on Practice' and how discomfort and vulnerability can become an impediment to authentic critical reflection and transformational learning. This paper is written from my perspective, as an emerging social worker to uncover how the integration of Boler's 'pedagogy of discomfort' and practices of self-compassion into Fook's model of critical reflection can heighten awareness, deepen reflective possibilities, and create more flexible selves. Including a 'pedagogy of discomfort' into critical reflection can serve to guide practitioners and students through the vulnerable process of uncovering cognitive, affective, and habitual patterns linked to dominant ideologies and hegemonic forces. The inclusion of self-compassionate teachings into the model of critical reflection better equips practitioners and students with tools to withstand the emotional labour that results from discomfort and reflection. With these tools, practitioners can reconstruct their experiences with new insights to engage in transformational change for personal and professional growth.